Schriftliches Peer-Textfeedback unter Studierenden: Auseinandersetzungen mit dem Inhalt von fremdem Text. Ergebnisse der qualitativen Inhaltsanalyse von 6 retrospektiven Interviews - von Gunten, Anne (Linguistik Online, 2018)
The paper at hand presents the results of a substudy from a 3-year research project carried out by the Bern University of Teacher Education, investigating how student teachers in their 1st semester deal with the content of other students’ texts when writing peer text feedback without guidance. In this study six future teachers were asked to substantiate their comments in retrospective verbalizations (see Linnemann 2017: 339) immediately after having written their text feedback. The transcriptions of the verbalizations were evaluated through thematic qualitative text analysis (see Kuckartz 2012). Whilst the result presentation is mainly category based, some case related results are also singled out, with a view to deriving observations for higher education teaching.